The Role of Empathy as a Path to Intimacy - Mijuskovic, Ben Lazare (Paedagogia Christiana, 2020)
The fear of absolute loneliness is the universal drive in all human beings. The opposite of loneliness is intimacy. Both are intense modes of human consciousness. Intimacy is secured through empathy, which is based on a mutual relationship of shared trust, respect and values, as well as a mutual sharing of feelings, meanings and affection. The dynamics of both intimacy and empathy – unlike sympathy and pity – must be mutual; whether it is expressed between two human beings, or between a person and the Lord through the power of prayer.